Implementing Sustainable Finance and Green Accounting Practices: Benefits and Challenges - Fitriani, Fitriani (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the implementation of sustainable financial practices and green accounting practices and their impact on company performance. A comprehensive literature review was conducted by collecting and analyzing related articles from various sources. The results reveal that sustainable financial practices and green accounting practices play an important role in improving corporate environmental and financial performance. However, there are several challenges faced in implementing this practice, including limited data, regulatory barriers, and lack of stakeholder awareness. Future studies are recommended to develop a more structured framework, conduct further empirical research, and expand regional understanding of the impact of sustainable financial practices and green accounting practices.